Pendampingan Strategi Komunikasi Pemasaran Melalui Instagram Pada Dinas Perdagangan Dan Perindustrian Kota Bogor - Rosadi, Reysi Resmidianti; Mulyana, Mumuh; Supriadi, Yoyon (Jurnal Abdimas Dedikasi Kesatuan, 2025)
Economic growth is one of the important indicators in the success of national development. In terms of national economic growth, small and medium industries (IKM) which are also part of micro, small and medium enterprises (UMKM) are considered to be able to play an important role in driving economic growth. The use of social media is spreading faster than before. One of the goals of social media is in the application of marketing communications. To advance the products of Small and Medium Industries in Bogor City, of course, it cannot be separated from the role of more interesting and dynamic marketing communications.The objectives of the study are: 1) To determine the marketing communication strategy for small and medium industry products through Instagram social media at the Bogor City Trade and Industry Office; 2) To determine the obstacles in implementing the marketing communication strategy for small and medium industry products through Instagram social media at the Bogor City Trade and Industry Office; 3) To determine efforts to deal with obstacles in implementing the marketing communication strategy for small and medium industry products through Instagram social media at the Bogor City Trade and Industry Office.The results of the study show that: 1) Social Media, Instagram is managed very well by the Trade and Industry Service in providing information and interesting content from Small and Medium Industry products in the city of Bogor; 2) The obstacle faced is the difficulty of increasing insight to reach Instagram users outside the followers of the Bogor City Trade and Industry Service Instagram account; 3) The efforts to deal with obstacles are trying to publish content related to Small and Medium Industry products more often and being accurate in providing information related to these IKM products.Keywords: Marketing Communication, Instagram Social Media, IKM